cDNA cloning of MAP kinase kinase reveals kinase cascade pathways in yeasts to vertebrates. - Kosako, H (1993)
A Xenopus 45 kDa protein has been identified as an immediate upstream factor sufficient for full activation of MAP kinase, and is shown to be capable of undergoing autophosphorylation on serine, threonine and tyrosine residues. In this study, we show that purified 45 kDa protein can phosphorylate a kinase-negative mutant of Xenopus MAP kinase on tyrosine and threonine residues, suggesting that the 45 kDa protein functions as a MAP kinase kinase to activate MAP kinase. We then report the cloning and sequencing of a full-length cDNA encoding this 45 kDa MAP kinase kinase, and show that it is highly homologous to four protein kinases in fission and budding yeasts: byr1, wis1, PBS2 and STE7. These yeast kinases are therefore suggested to function as a direct upstream activator for a presumed MAP kinase homolog in each signal transduction pathway involved in the regulation of cell cycle progression or cellular responses to extracellular signals. Finally, we report bacterial expression of recombinant MAP kinase kinase that can be phosphorylated and activated by Xenopus egg extracts.